Optimal process capacity allocation under abnormal conditions - Gumilao, T. K. (Animo Repository, 2020)
Plant operations may need to be optimized in response to abnormal conditions resulting from various disruptive events. In such cases, it is of interest to minimize interim economic losses by allocating the capacities of process units optimally while the plant operations deviate from the nominal design conditions. This note extends the mixed integer linear programming (MILP) model previously developed by Kasivisvanathan et al. (Applied Energy 102: 492–500, 2013) by considering the effect of financial penalties for failure to meet contractual obligations to customers; it is assumed that such penalties are paid in direct proportion to the magnitude of production deficit. The extended model is illustrated with a case study of a chlor-alkali industrial complex, and general implications of the results are discussed. © 2020, Springer Nature Singapore Pte Ltd.